Prevalence of Hepatitis B virus Infection Among Cataract Patients in South-East Nigeria - Onwuegbuna, Arinze Anthony; Chianakwalam, Emeka Akujuobi; Amobi, Miriam-Benigna Chika; Apakama, Akunne Ijeoma; Okosa, Chuka Michael; Chigbo, Chisom God’swill; Eleje, George Uchenna (Journal of Ophthalmology and Research, 2021)
Background: Hepatitis B Virus (HBV) is a public health issue especially in sub-Saharan Africa. This is because attention has not been given to this potentially lethal viral infection especially in cataract patients which will need extraordinary safety measures. Cataracts remain the commonest cause of blindness in Nigeria and globally. We are yet to know the prevalence of HBV when co-existing cataract among patients in Nigeria. Objective: To assess the prevalence of hepatitis B virus infection among cataract patients in southeast Nigeria. Materials and methods: This single hospital-based, cross-sectional quantitative study was conducted among cataract patients that underwent cataract surgery at City of Refuge Specialist Eye Clinic Onitsha, Nigeria between September 1, 2020 and February 28, 2021. The patients were tested for HBV through rapid testing and confirmed via Enzyme-Linked Immunosorbent Assay. Patients diagnosed with cataract and had HBV infection were included. The primary outcome measure was the number of cataract patients with co-existing HBV infection. The case files of all who had a diagnosis of cataract during the period were retrieved from the Medical Record Department of the hospital to extract relevant information and demographic data. Data was entered into Excel spreadsheet and exported to SPSS version 26 IBM Corporation for analysis. Bivariate analysis was conducted to identify significant variables with a P value < 0.05 considered statistically significant. Results: In this study, 423 participants who underwent cataract surgery during the study period were included, of which 5 (1.2%) were HBV seropositive. The prevalence of HBV among cataract patients was 1.2%. Majority (53.71%) of patients were between the ages 60 and 74 years, and the female: male ratio was 1:1. The prevalence of HBV among cataract patients was not affected by rural